2010
DOI: 10.1186/1465-9921-11-90
|View full text |Cite
|
Sign up to set email alerts
|

Azithromycin attenuates airway inflammation in a mouse model of viral bronchiolitis

Abstract: BackgroundViral bronchiolitis is the leading cause of hospitalization in young infants. It is associated with the development of childhood asthma and contributes to morbidity and mortality in the elderly. Currently no therapies effectively attenuate inflammation during the acute viral infection, or prevent the risk of post-viral asthma. We hypothesized that early treatment of a paramyxoviral bronchiolitis with azithromycin would attenuate acute and chronic airway inflammation.MethodsMice were inoculated with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(80 citation statements)
references
References 51 publications
3
72
0
5
Order By: Relevance
“…27 Azithromycin has also been shown to reduce illness severity in a mouse model of viral bronchiolitis. 28 Thus, azithromycin has the potential to have direct antiviral activity by augmenting the production of those interferons that we have already shown to be deficient in asthma exacerbations, 20,26 and this activity may make it a better treatment option than telithromycin, which does not appear to have this property. 27 A further mechanistic aim of our study, therefore, was to investigate the frequencies of standard bacterial, atypical bacterial and viral infections in these exacerbations to determine the relative importance of each of these infections, and of possible coinfections with one or more agents, in the aetiology of acute exacerbations of asthma in adult subjects.…”
Section: Mechanisms Of Activity Of Macrolide/ketolide Antibiotics In mentioning
confidence: 99%
“…27 Azithromycin has also been shown to reduce illness severity in a mouse model of viral bronchiolitis. 28 Thus, azithromycin has the potential to have direct antiviral activity by augmenting the production of those interferons that we have already shown to be deficient in asthma exacerbations, 20,26 and this activity may make it a better treatment option than telithromycin, which does not appear to have this property. 27 A further mechanistic aim of our study, therefore, was to investigate the frequencies of standard bacterial, atypical bacterial and viral infections in these exacerbations to determine the relative importance of each of these infections, and of possible coinfections with one or more agents, in the aetiology of acute exacerbations of asthma in adult subjects.…”
Section: Mechanisms Of Activity Of Macrolide/ketolide Antibiotics In mentioning
confidence: 99%
“…Clarithromycin and azithromycin have been shown to be efficient in reducing airway inflammation, the former having been associated with decreased airway edema and decreased TNF-α, IL-1, and IL-10 concentrations in nasal aspirates. (8,44,45) One group of authors demonstrated that azithromycin decreased IL-5 production in lymphocytes of children with atopic asthma, without affecting IFN-Îł production, thereby showing that azithromycin has a beneficial effect on the pathogenesis of asthma. (40) Even with all of these theoretical justifications based on experimental or mechanistic studies, (46) the positive effects of macrolides has not been consistent in the published clinical trials in Anti-inflammatory effects of macrolides in childhood lung diseases J Bras Pneumol.…”
Section: Asthmamentioning
confidence: 99%
“…(7) Other reported effects include reduced goblet cell secretion, reduced bronchoconstriction induced by a decreased release of endothelin-1, and inhibition of the cholinergic response in the airway smooth muscle. (2,8) A summary of the anti-inflammatory mechanisms is provided in Chart 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Azithromycin is an azalide, a subclass of macrolide antibiotics 9) . Some case reports have suggested that macrolides have the potential to enhance the anticoagulation effect of warfarin [1][2][3] .…”
Section: Introductionmentioning
confidence: 99%